On-Surface Synthesis and Real-Space Visualization of Aromatic P3N3 - Zhong, Qigang; Mardyukov, Artur; Solel, Ephrath; Ebeling, Daniel; Schirmeisen, André; Schreiner, Peter R.; Justus Liebig University Giessen (My University, 2023)
On-surface synthesis is at the verge of emerging as the method of choice for the generation and visualization of unstable or unconventional molecules, which could not be obtained via traditional synthetic methods. A case in point is the on-surface synthesis of the structurally elusive cyclotriphosphazene (P3N3), an inorganic aromatic analogue of benzene. Here, we report the preparation of this fleetingly existing species on Cu(111) and Au(111) surfaces at 5.2 K through molecular manipulation with unprecedented precision, i.e., voltage pulse-induced sextuple dechlorination of an ultra-small (about 6 Å) hexachlorophosphazene P3N3Cl6 precursor by the tip of a scanning probe microscope. Real-space atomic-level imaging of cyclotriphosphazene reveals its planar D3h-symmetric ring structure. Furthermore, this demasking strategy has been expanded to generate cyclotriphosphazene from a hexaazide precursor P3N21 via a different stimulation method (photolysis) for complementary measurements by matrix isolation infrared and ultraviolet spectroscopy.
Keywords: ddc:540